Contemporary and Beyond? - Szabó, Éva (Hungarian Journal of English and American Studies, 2021)
Book review:Acheson, James, ed. The Contemporary British Novel Since 2000. Edinburgh UP, 2017. 214 pages. ISBN 978 1 4744 0375 7. epub. £80.00.